John Forsyth papers - Forsyth, John, 1780-1841.
Correspondence, accounts, and other papers relating to Forsyth's duties as U.S. minister to Spain and as U.S. secretary of state. Also includes a diary of a journey on the ship Othello from Bordeaux to New York.
In part, positive and negative photocopies.
U.S. senator, representative, secretary of state, and the governor of Georgia.
Collection material in English.
Keywords: United States. -- Department of State; Othello (Ship : 1807); Voyages and travels; Spain -- Foreign relations -- United States; United States -- Foreign relations -- Spain; Cabinet officers; Governors -- Georgia; Representatives, U.S. Congress -- Georgia; Senators, U.S. Congress -- Georgia